2003
DOI: 10.1063/1.1614875
|View full text |Cite
|
Sign up to set email alerts
|

Simplified system based on photoelastic modulation technique for low-level birefringence measurement

Abstract: In this article, the authors present a new low-level birefringence detection (LLBD) system based on the use of a photoelastic modulator. This system uses a single modulator so that only one detector is required to capture all the frequency components in the optical beam. The design removes gain errors associated with the conventional dual-beam approach. In addition, we also incorporate a complete analytical signal-processing algorithm to enhance measurement accuracy by eliminating the requirement of small phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Ho and coworkers reported various configurations for phase measurement using photoelastic modulators since 2003 [56,59,44]. As shown in Fig.…”
Section: Polarimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Ho and coworkers reported various configurations for phase measurement using photoelastic modulators since 2003 [56,59,44]. As shown in Fig.…”
Section: Polarimetrymentioning
confidence: 99%
“…By decomposing the detected signal using a lock-in amplifier with the input fed by reference signals at the first and second harmonic frequencies of the modulator, the amplitudes of first and second harmonics can be obtained and further processed to determine the phase retardation. This scheme was first used to determine the low-level birefringence [44], and later adopted for SPR biosensing [56]. Phase change with regard to varying concentration of glycerin in water were measured and the sensitivity was found to be 1.19 × 10 −6 RIU.…”
Section: Polarimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…With all the necessary information already embedded in the frequency domain of the detected signal, the polarization state is extracted by analyzing the first and second harmonics of the modulated signal as well as the DC component simultaneously. In previous work we reported that the influence of residual birefringence to phase retardation of PEM [15,17]. In order to minimize this effect, the setup is located in an enclosed environment to ensure minimum temperature fluctuation caused by air circulation and proprietary frequency generator is used to provide stable modulation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Besides AOM, a photoelastic modulator (PEM) can also be used to modulate the laser frequency. Peng et al developed a single-beam approach where the input beam is modulated by a PEM and the SPR-induced phase change was obtained by an analytical signal-processing algorithm [38]. This single-beam system was then used for real-time monitoring of biomolecule binding reactions with detection sensitivity up to 6 × 10 −7 RIU or 15 ng/ml [39,40].…”
Section: Phase Interrogation Sprmentioning
confidence: 99%